2016
DOI: 10.1080/09593330.2016.1201545
|View full text |Cite
|
Sign up to set email alerts
|

The variability and causes of organic carbon retention ability of different agricultural straw types returned to soil

Abstract: Retaining the organic carbon (C) content of agricultural straw when returned to soil is restricted by rapid decomposition. In order to clarify the difference in returned straw decomposition and the causes, and to develop a straw returning mode with high-efficiency of organic C accumulation, the decomposition processes of corn, soybean, rice and wheat straws were systematically studied in fields. When returned in situ (the original planting area), the C in soybean straw was decomposed most quickly with a decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…It is almost alarming that in an annual application of wheat straw (5 t DM ha −1 = 2140 kg C ha −1 ) C SOM also decreased (by 8%). It is obvious that straw is relatively quickly mineralized after its incorporation into the soil [ 24 , 25 , 26 , 27 ]. Due to this fact it is clear that cereal straw application itself cannot improve the soil organic matter content and quality.…”
Section: Discussionmentioning
confidence: 99%
“…It is almost alarming that in an annual application of wheat straw (5 t DM ha −1 = 2140 kg C ha −1 ) C SOM also decreased (by 8%). It is obvious that straw is relatively quickly mineralized after its incorporation into the soil [ 24 , 25 , 26 , 27 ]. Due to this fact it is clear that cereal straw application itself cannot improve the soil organic matter content and quality.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was then transferred to a tube furnace under an N 2 atmosphere. Next, the mixture was calcined at different temperatures (400, 500, 600, 700, 800, and 900 C) and different pyrolysis times (30,60, and 90 min). The heating and cooling rates were 10 C/min, and 20 C/min, respectively.…”
Section: Preparation Of Multivalent Iron-loaded Biochar (Fe@bc)mentioning
confidence: 99%
“…27 Biochar, as a reducing agent, to reduce iron oxide at high temperatures, avoids not only the shortcomings of the impregnation method but also form more active sites on the surface of the activator. 28,29 Soybean straw, a candidate material for biochar, has the highest carbon content (41.0%-47.8%), lowest nitrogen content, 30,31 and the highest C/N and cellulose/N compared to wheat, corn, cotton, and others. 31 Further, ash generated by the high-temperature pyrolysis of soybean straw is negligible, and the carbonization rate is high.…”
mentioning
confidence: 99%
“…Straw returning to fields is a widely used agricultural practice to enhance soil fertility and increase the organic matter content, which leads to lower CO 2 emissions and alleviates air pollution problems compared to straw burning . An 8 year field experiment indicated that the physical, chemical, and biological properties of soil were considerably improved after the application of rice straw in an upland cropping system .…”
Section: Introductionmentioning
confidence: 99%